Poder, clientelismo e violência política no Zimbabwe: a Terceira Chimurenga - Victor Hugo Nicolau (Cadernos de Estudos Africanos)
The conflicts which are today manifest in Zimbabwean society are the result of cumulative pressures stemming from unjust situations inherited from the colonial past, from a serious economic crisis, and from the increasing inefficiency of an autocratic political system. The vast majority of internal and external observers have put aside the notion that the racial dimension constitutes an autonomous factor in the conflict. It is at this stage generally accepted that the main conflicts present in contemporary Zimbabzean society can be included in three clearly identified areas: 1) an area of economic and social conflicts, 2) an area of fundamentally political conflicts, 3) an area of regional and ethnic conflicts.